Possible Implication of Nrf2, PPAR-γ and MAPKs Signaling in the Protective Role of Mangiferin against Renal Ischemia/Reperfusion in Rats - Abdallah M. Gendy; Amira A. El-Gazar; Ghada M. Ragab; Asmaa K. Al-Mokaddem; Alaadin E. El-Haddad; Heba Mohammed Refat M. Selim; Einas Mohamed Yousef; Najat O. Hamed; Sherihan Salaheldin Abdelhamid Ibrahim (MDPI AG, 2022)
Mangiferin (Mang) is a known glucosylxanthone that has proven its shielding effect against ischemia/reperfusion (Is/R). However, its full underlying mechanistic perspective against renal Is/R induced lesions is not fully revealed. Consequently, the purpose of this study is to track further non-investigated modulatory signals of Mang against the renal Is/R model involving nuclear factor erythroid 2-related factor (Nrf)2/heme oxygenase (HO)-1, peroxisome proliferator-activated receptor (PPAR)-γ/nuclear factor (NF)-κB, p38 mitogen-activated protein kinase (MAPK), and c-Jun N-terminal kinase (JNK) signaling. To ratify our aim, Mang was administrated (20 mg/kg, i.p for seven days) before the induction of bilateral Is/R. Mechanistic maneuver revealed that Mang balanced oxidative state via increasing the expression of the antioxidant Nrf2/HO-1 cue with subsequent enhancement of GSH besides MDA lessening. Additionally, Mang enhanced PPAR-γ mRNA expression and declined p-p38 MAPK and p-JNK expression with concomitant NF-κB downsizing leading to iNOS/NOx and TNF-α rebating. Furthermore, the Mang anti-apoptotic trait was affirmed by enriching Bcl-2 expression as well as decreasing Bax and caspase-3 expression. All these potentials were in the line with the molecular docking results and the improved histopathological findings and renal function biomarkers. Consequently, Mang provided plausible protective mechanisms against renal Is/R-related events, possibly by amending oxidative status, inflammatory mediators, and apoptotic cell death through the involvement of Nrf2, PPAR-γ, MAPK, JNK, and NF-κB signaling.